Reason and Revelation in the Tafsir Al-Kashshaf: Mu'tazilah's Study of the Verses of Tanzih I'tiqodiyah - Alniatul Fadilah; Muh. Fathoni Hasyim; Abdul Qudus Al Faruq; Hilmi Faiz Azzam (Universitas Nurul Jadid, 2025)
The study of Qur'anic interpretation continues to develop along with the dynamics of Islamic thought, one of which is through the pattern of kalām interpretation developed by the Mu'tazilah. Tafsir al-Kashshāf by al-Zamakhsharī is one of the main representations of the Mu'tazilah rational approach in understanding the verses of tanzīh i'tiqādiyyah. This study aims to analyze the epistemological relationship between reason and revelation in the interpretation, especially in interpreting the concepts of divinity, divine justice, and human free will. In this context, a methodological dilemma arises between the authority of reason as the main interpretive instrument and the authority of revelation as a source of transcendent truth, which is problematic in the discourse of interpretation—both historically and contemporary. Using qualitative methods based on literature studies and content analysis of the interpretation text, this study found that al-Zamakhsharī emphasized the supremacy of reason in interpreting verses containing elements of anthropomorphism, and rejected literal interpretations that have the potential to equate God with creatures. This interpretation consistently prioritizes linguistic and logical approaches to maintain the purity of the concept of monotheism. This study contributes to understanding the epistemological construction of Mu'tazilah interpretation and opens up opportunities for the development of contemporary interpretation methodology that is rational-transcendental and contextual.